Evaluasi Respons Struktural Pondasi Mesin Kapal Polbeng 2 Menggunakan FEM: Pendekatan Multi-Material dan Analisis Dinamis - Angrayni, Septi Ayu; Audina, Nur; Roher, Fahendi (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The engine foundation is a critical structural element in a ship’s propulsion system because it functions to withstand static loads, dynamic loads, and vibrations generated by the engine. The Polbeng 2 vessel experienced a significant change in the form of a main engine replacement, which affected the magnitude of the load, support points, and vibration characteristics. This study aims to evaluate the structural response of the engine foundation using the Finite Element Method (FEM) by involving three types of materials: fiberglass, hybrid composite (glass–carbon), and carbon fiber composite. The analyses conducted include static structural analysis, modal analysis, and harmonic response to detect potential resonance. The results show that the carbon fiber composite exhibits the lowest von Mises stress of 0.009 MPa and the minimum deformation of 0.24 mm. Modal analysis indicates that the natural frequencies of the structure fall within the range of 300–520 Hz, which is far from the engine excitation frequency (110–220 Hz), thus minimizing the risk of resonance. This study confirms that optimizing the material and foundation configuration provides significant improvements to the structural performance and service life of the ship’s propulsion system.